(3GdJYhjV Yf GdVQQ GdWHj hGdJCejf ef eSFhdjI GdCWHGA GdeOfjI (B/s - (3YeGO GdOjf, HQcGJs; (3Medjd, UGdMs ((3GdEScfOQjI, eUQ (B:s (3OGQ GdacQ GdLGeYj,s, 2017)
(3jJfGhd cJGH (B((3GdJYhjV Yf GdVQQ GdWHj hGdJCejf ef eSFhdjI GdCWHGA GdeOfjI(B) (3hGdPj bGe HJCdjag (B((3HQcGJ YeGO GdOjf(B) (3aj MhGdj (B(257) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdeSFhdjI GdeOfjI ddCWHGA hGdJYhjVGJ(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdaUd GdChd (B: (3BdjGJ GdJYhjV Yf GdVQQ GdWHj, GdeHMK GdChd (B: (3CMcGe GdVQQ aj GdeSDhdjI GdeOfjI GdWHjI, GdeWdH GdChd (B: (3eaghe GdVQQ GdWHj, GdaQY GdChd (B: (3GdJYQja HGdVQQ GdWHj (B... (3EdN(B.s
(3HHdjhLQGajI (B: (3UaMI (B233-248.s
Keywords: (3GdeSFhdjI GdeOfjI ddCWHGAs; (3GdNWC (B((3bGfhf(B)s; (3GdJYhjVGJs -- (3bhGfjf hJTQjYGJs